2020
DOI: 10.3390/ijerph17134729
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Research Evolution on the Socio-Economic and Environmental Dimensions on University Social Responsibility

Abstract: Responsible higher education institutions have an impact on society and economic, environmental, and social development. These effects define the axes of the socially responsible management of the universities. The concept of university social responsibility (USR) manages these relationships to produce a positive impact on society through higher education, research, and the transfer of knowledge and technology, as well as education for sustainability. For this study, worldwide research into this subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 117 publications
(150 reference statements)
0
64
0
9
Order By: Relevance
“…Through this collaboration, which, as mentioned above, is not excessive [ 76 ], Spanish healthcare organizations and companies related to the sector can access innovative ideas that lead to lines of business and transfer to the market and society, obtain new funding channels, and enter new markets due to the knowledge provided by scientific groups abroad regarding the mindset of these countries. These groups can even help YRS to carry out their mobility abroad so that, to the benefit of all, they can open up new possibilities for international collaboration with advanced countries, which have a greater capacity to mobilize economic and human resources and attract new partners [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through this collaboration, which, as mentioned above, is not excessive [ 76 ], Spanish healthcare organizations and companies related to the sector can access innovative ideas that lead to lines of business and transfer to the market and society, obtain new funding channels, and enter new markets due to the knowledge provided by scientific groups abroad regarding the mindset of these countries. These groups can even help YRS to carry out their mobility abroad so that, to the benefit of all, they can open up new possibilities for international collaboration with advanced countries, which have a greater capacity to mobilize economic and human resources and attract new partners [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small sample sizes may have resulted in limited power to detect true difference-in-differences between groups. Furthermore, college is a natural period of transition in the life course, and new experiences are especially salient during the first months and year in school [ 14 ]. As such, it should be noted that a greater proportion of comparison students were in their first year of school and participated during Fall quarter.…”
Section: Discussionmentioning
confidence: 99%
“…Intervening in college and university settings is promising given these institutions’ (1) high levels of unilateral control, (2) broad reach, (3) pro-social missions, and (4) widespread commitment to promoting wellbeing [ 10 , 11 , 12 , 13 ]. Indeed, growing interest in university social responsibility (USR) may motivate higher education stakeholders to implement interventions targeting health and sustainability [ 14 ]. Koutali (2019) describes the potential of USR for developing agency among students and translating academic knowledge to broader society [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through this method, which has been used in more than 3200 investigations, the most relevant aspects of the subject under study were identified and described. Mainly, aspects such as evolution, trends, key actors (authors, countries, journals, institutions), and the identification of keywords and semantic structure of research [90,91]. These last two variables were represented by bibliometric maps constructed with VOSviewer software, version 1.6.11., Leiden University, Leiden, The Netherlands.…”
Section: Methodsmentioning
confidence: 99%